Assessing of sustainable and integrated waste management in the prefecture of Marrakech, based on the “wasteaware” model - BOULKHIR , Hanane; ARIB , Fatima (African Scientific Journal, 2024)
Abstract This article proposes a set of indicators for assessing the integrated and sustainable management of household and similar waste, drawing on UN-Habitat’s pioneering work in global solid waste management. The analytical framework divides the urban solid waste management system into two interconnected "triangles": one covering physical aspects such as collection, recycling, and disposal, and the other focusing on governance dimensions, including inclusiveness, financial viability, and the strength of institutions and policies. Using the case of the Marrakech prefecture, with a population of 1,405,373 and an urbanization rate of 74%, the article highlights the evolution of waste management practices, particularly after the establishment of the city’s waste disposal and recovery center in 2020. The study identifies both strengths and areas for improvement in the local waste management system, providing a strategic basis for future enhancements. Despite key advancements, challenges such as low recycling rates and informal waste recovery continue to hinder progress towards a circular economy. Abbreviations: CEV ,Centre d’Elimination et de Valorisation ;CNSS, Caisse Nationale de Sécurité Sociale ;GNI, Gross National Income ;PNVD :Plan National de Valorisation des Déchets ;SNRVD :Stratégie Nationale de Réduction et de Valorisation des Déchets . Keywords: “ wasteaware ” model; Household and similar waste ; Integrated Sustainable Waste Management ; Marrakech prefecture.